(untitled) (Development Service Industry Management, 2025)
Modern conditions of socio-economic development of Ukraine necessitate the formation of new approaches to regional policy aimed at activating internal investment resources and increasing the efficiency of their use. This issue becomes especially relevant in the context of decentralization and post-war recovery, when regions act as key actors of economic transformation and a space for developing competitive economic models. Effective mobilization of internal investment resources is considered a strategic instrument for ensuring sustainable territorial development, strengthening local economies, and reducing dependence on external sources of financing. Despite the growing interest in involving local capital in development projects, mechanisms for supporting internal investments at the regional level remain insufficiently systematized and require scientific justification. The purpose of the article is to substantiate the theoretical foundations and practical mechanisms for attracting internal investment resources, as well as to define directions for improving their efficiency to ensure sustainable regional development.The theoretical basis of the study consists of research conducted by Ukrainian and foreign scholars in the fields of regional economics, investment management, and financial decentralization. The information base includes regional development strategies, social and economic development programs of Ukrainian regions, as well as analytical data on the investment activity of territorial communities. The research employs methods of systems approach, structural-functional analysis, content analysis of strategic documents, comparative studies, and elements of case study. The article identifies the conceptual characteristics of internal investment resources and their role in ensuring economic growth at the regional level. Existing instruments for attracting investments in Ukrainian regions are analyzed, including the development of regional business support funds, mechanisms of public-private partnership, community participation in project budgeting, and the use of municipal bonds. It is revealed that regional development policies create a basis for forming an effective system of stimulating internal investments; however, they require expanding the mechanisms of financing local projects and strengthening the institutional environment. Further research should focus on the development of a model of regional governance of internal investment resources, assessment of the potential for financial self-sufficiency of territorial communities, as well as the design of tools for enhancing investment activity of small and medium-sized enterprises. The practical value of the study lies in the formulation of recommendations for local authorities, business entities, and development institutions regarding the implementation of an effective system for attracting internal investment resources as a factor of sustainable economic growth of Ukrainian regions.